Effect of kafirin-based films incorporating citral and quercetin on storage of fresh chicken fillets - Giteru, S.; Oey, I.; Ali, M.; Johnson, Stuart; Fang, Z. (Pergamon, 2017)
This study investigated mechanical and bioactive properties of kafirin films consisting of 2.5% citral (CK), 2% quercetin (QK) or 1.25% citral + 1% quercetin (CQK). Incorporation of citral reduced the maximum stress (smax) and stiffness, accompanied by an increase in the strain at break (eb), and yield stress (sy) of the films. Compared to the plain kafirin films (PK) and QK, citral–containing films showed significant antimicrobial activity (p < 0.05) against the total viable count on chicken fillets stored at 2 ± 0.5 °C for 96 h. The final thiobarbituric acid reactive substances (TBARS) were lower for PK, CQK, and QK (0.18, 0.16 and 0.23 mg MDA/kg respectively), compared to unwrapped fillets and CK (0.41 and 0.59 mg MDA/kg respectively). These findings implied that quercetin and those polyphenolics likely co-extracted with kafirin possessed the ability to inhibit the development of lipid oxidative products. CIE L*a*b* colour values showed pronounced yellowness (b*) of wrapped samples. This colouration was attributed to the sorghum phytochemical co-extracted with the kafirin, and the intrinsic colour of citral, and quercetin. Kafirin edible films incorporating citral and quercetin demonstrated potential as a packaging material to improve food safety and quality of the chicken.